Analisis Kebijakan & Kekuasaan Pada Pendidikan - Mohamad Fatih; Cindya Alfi; Syamsul Hadi (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2023)
Power and educational policy are inseparable because the exercise of power shapes the outcome of the policy process. In addition, because power relations are institutionalized within the school system, school administrators have power through their organizational positions. Through literature review and research results that are relevant to policy and power in education and schools. Their power ultimately lies in their institutions and the policies and traditions behind them, not in their characteristics. As their authority weakens, educators must learn to use other kinds of power, and understand power relations in policy circles. Therefore, developing an understanding of power is very important for educational leaders